Hypoperfusion During Migraine and its Effect on the Retina - Dr. Ahmad Nezar Abdulhamid; Dr. Daniah Radhi Abed; Dr. Sameer Hameed Hammadi (Zien Journals, 2023)
One of the most prevalent chronic, complex neurovascular illnesses, migraine, is primarily defined by recurring bouts of incapacitating headaches with aura appearances in up to one-third of patients. Nearly 15% of people get migraines, making it the third most common sickness in the world. Objective: This paper aims to study hypoperfusion during migraines and its Effect on the Retina
Keywords: RNFL thickness; migraine; symptoms